Investigation of the antiviral activity of the recombinant human interferon lambda 1 in human conjunctiva cell culture - N. A. Kikhtenko; T. N. Ilyicheva; A. G. Durymanov; A. Zh. Fursova; P. G. Madonov (Сибирский научный медицинский журнал, 2021)
The aim of the study was to determine the efficacy of recombinant human interferon lambda 1 (IFN-λ1) against human adenovirus serotype 5 in a culture of human conjunctival cells Chang conjunctiva clone 1-5c-4. Material and methods. The study design consisted of three experimental schemes, reflecting a prophylactic and two options for a therapeutic and prophylactic treatment regimen (with the constant presence of the virus in the culture medium and with its removal after adsorption). The antiviral activity of IFN-λ1 was determined by the number of viable cells after exposure to the virus (MTT test). Results and discussion. It has been established that IFN-λ1 has antiviral activity against human adenovirus in vitro under a prophylactic and therapeutic-prophylactic scheme of administration at an infection dose of 1 and 10 TCID50 (50% tissue culture infectious dose), but not at an infection dose of 100 TCID50. The antiviral effect of the use of IFN-λ1 in a therapeutic and prophylactic regimen at an infection dose of 1 TCID50 was comparable to that of IFN-α. At the same time, both interferons did not have a toxic effect on the cell culture even at a concentration of 84 and 58 μg/ml, respectively. The antiviral activity and the absence of cytotoxic action provide the basis for further study of the possibility of development of based on IFN-λ1 drug for eye conjunctiva viral diseases treatment.